INTERACTIONS BETWEEN CETYLTRIMETHYLAMMONIUM OR TETRAMETYLAMMMONIUM BROMIDE AND MCl2 OR MCl5 (M = Hg, Cu, Zn, Co, Ni, Cd and Nb) IN MONONUCLEAR COMPLEXES: SYNTHESIS AND INFRARED STUDY - DAME SEYE (Alma Mater Publishing House "Vasile Alecsandri" University of Bacau, 2020)
On allowing cetyltrimethyl ammonium bromide (C19H42NBr) and HgCl2, CuCl2.2H2O, CoCl2.6H2O, ZnCl2, NiCl2.6H2O or NbCl5 in specific ratio in methanol, new mononuclear have been obtained and studied by infrared. The suggested structures are discrete, of infinite chain with octahedral or tetrahedral environments around the metallic centres. The MX2 behaves as discrete chains. For most of the structures, when intermolecular hydrogen bonds are considered, supramolecular architectures may be obtained.